2015
DOI: 10.1175/jamc-d-14-0223.1
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of the Nocturnal Boundary Layer Evolution on a Slope at the Foot of a Desert Mountain

Abstract: Observations were taken on an east-facing sidewall at the foot of a desert mountain that borders a large valley, as part of the Mountain Terrain Atmospheric Modeling and Observations (MATERHORN) field program at Dugway Proving Ground in Utah. A case study of nocturnal boundary layer development is presented for a night in mid-May when tethered-balloon measurements were taken to supplement other MATERHORN field measurements. The boundary layer development over the slope could be divided into three distinct phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The total depth of the katabatic layer (not shown) deepens through the ET at all sites, typically exceeding the height of the towers within 2 h of local sunset. In their case‐study during the spring campaign, Lehner et al () reported an approximate katabatic depth of 30 m through the ET, observed with a tethered balloon system located between ES2 and ES3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total depth of the katabatic layer (not shown) deepens through the ET at all sites, typically exceeding the height of the towers within 2 h of local sunset. In their case‐study during the spring campaign, Lehner et al () reported an approximate katabatic depth of 30 m through the ET, observed with a tethered balloon system located between ES2 and ES3.…”
Section: Resultsmentioning
confidence: 99%
“…Due to frequent valley interaction at all ES towers, which typically occurs later into the night (Lehner et al, ; Grachev et al, ), this study focuses on the timing and structure of the katabatic flow through the ET. Here, we have defined the ET as 1 h before to 3 h after local sunset, where local sunset is defined at each site as the moment where the direct insolation drops to zero as the shadow front eclipses the tower.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…the Alps, Rotach et al, 2004;Nadeau et al, 2013, or Salt Lake Valley, Doran et al, 2002Monti et al, 2002). However, shallow drainage flows (SDFs) or density currents have been less studied (Mahrt et al, 2001;Soler et al, 2002;Udina et al, 2013;Oldroyd et al, 2014;Lehner et al, 2015a), in part because of their smaller scale, that often makes them more difficult to detect. Their proximity to the surface and their ability to change the surface conditions make them important and interesting phenomena worthy of analysis in SBL studies.…”
Section: Introductionmentioning
confidence: 99%